Gold Nanoparticles with Selective Antileukemic Activity In Vitro and In Vivo Target Mitochondrial Respiration. Issue 6 (6th March 2019) - Gaiser, Ann‐Kathrin; Hafner, Susanne; Schmiech, Michael; Büchele, Berthold; Schäfer, Patrick; von Arnim, Christine A.; Calzia, Enrico; Feuring‐Buske, Michaela; Buske, Christian; Vick, Binje; Jeremias, Irmela; Syrovets, Tatiana; et al.
Abstract: This study explores biocompatible amino‐functionalized gold nanoparticles (Au‐NH2 ) as nanotherapeutics for the selective eradication of leukemia cells, elucidates the mechanism of cytotoxicity, and it confirms in vivo efficacy of the engineered nanomaterial. Au‐NH2 trigger apoptotic cell death of myeloid leukemia cell lines and primary acute myeloid leukemia (AML) cells by i) inhibition of mitochondrial respiration, ii) ATP depletion, iii) loss of mitochondrial membrane potential, and iv) mitochondrial release of cytochrome c. Au‐NH2 act selectively on leukemia cells inasmuch as the viability of normal peripheral blood mononuclear cells and macrophages as well as the colony formation of hematopoietic stem cells remain basically unaffected. The selectivity of Au‐NH2 for AML cells can be attributed to both the preferential accumulation of AuNH2 in AML cells and the strong dependence of those cells on mitochondrial oxidative phosphorylation for ATP production. Importantly, Au‐NH2 applied either as monotherapy or as a cytarabine combination regimen possess antileukemic efficacy in the absence of adverse events in mice xenografted with primary human AML in vivo. The engineered material may pave the way for a novel nanotherapeutic treatment of AML. Abstract : Amino‐functionalized gold nanoparticles (Au‐NH2 ) exhibit high selective cytotoxicity against acute myeloid leukemia (AML) cells in vitro and in vivo. Au‐NH2 specifically target mitochondrial respiration essential for energy production in leukemia cells thereby inducing apoptosis. Notably, in a human AML xenograft model, leukemia progression is strongly antagonized by Au‐NH2 applied either as monotherapy or in combination with standard cytarabine chemotherapy.